Systematic Investigation of the Effects of Seven Plant Extracts on the Physiological Parameters, Yield, and Nutritional Quality of Radish (Raphanus sativus var. sativus) - Godlewska, Katarzyna; Pacyga, Paweł; Michalak, Izabela; Biesiada, Anita; Szumny, Antoni; Pachura, Natalia; Piszcz, Urszula (Frontiers in Plant Science, 2021)
The modern agricultural sector faces the challenge of addressing the needs of the fast-growing global population. This process should be both high yielding and sustainable, without creating risks for both the environment and human health. Therefore, natural products are gaining attention in the production of safe and nutritious food. In a systematic effort to develop affordable and effective biostimulants, we examined the impact of botanical extracts on the growth and physiological parameters of radish plants under field conditions. Ultrasound-assisted extraction, mechanical homogenisation, and water were used for the production of potential botanical biostimulants. Foliar applications of the bio-products developed and used in our study have led to an increase in the examined parameters (total yield, dry weight, photosynthetic pigments, vitamin C, nitrates, and micro and macroelements) was observed. A decrease in the total phenolic compounds content was also noted, as well as a varied impact on the volatile compounds, fatty acids, and sterol composition. The most beneficial effects on radish, in terms of physiological and biochemical properties, were found with the extracts of common dandelion, valerian, nettle, and giant goldenrod. This innovative approach in our study has provided a valuable tool for the sustainable horticultural production.